Gerakan Mahasiswa Dalam Pusaran Tiga Orde Kekuasaan: Antara Gerakan Moralis Atau Gerakan Politis - Elis Mardianti (Universitas Warmadewa, 2022)
Students as part of the intellectual group in Indonesia with their various movements have a very crucial role. In the three orders of power, students always show their existence in the national political process. In the old order era, students became one of the political forces with the presence of various organizations that actively participated in providing input to the current political system. Continuing with Suharto's rule, students with social movements were one of the reasons for the fall of the authoritarian regime that had been in power for a long time. The dynamics continue. After the change of government structure, even though the student movement of the reform order was often considered lost, it still showed its existence by providing input on government policies. Movements in this reform era often brought up quite new issues related to the environment or human rights. This study discusses the direction of the student movement with its various dynamics that occur in the vortex of the three orders of power. Social movement theory is used as an analytical tool in this research. This study also uses descriptive qualitative research methods and literature review techniques with primary data sources obtained through interviews with students who are actively involved in the student movement and secondary data whose sources are obtained from books, scientific articles, or mass media. The conclusion obtained from the results of this study is that the various movements launched by students are often moralist movements, although the realm of the movements often leads to the political realm. Students tend to move on the will and concerns of the people without trying to position themselves to achieve certain political power or position.